Evaluation of Immunoprotective Effects of Fusobacterium necrophorum Outer Membrane Proteins 43K OMP, Leukotoxin and Hemolysin Multi-Component Recombinant Subunit Vaccine in Mice - Xiao, Jiawei; Jiang, Jiancheng; He, Xianjing; Zhang, Siyao; Wang, Zhihui; Wang, Fengfeng; Wang, Lina; Guo, Donghua (Frontiers in Veterinary Science, 2021)
We evaluated the efficacy of three vaccine formulations containing different combinations of proteins (43K OMP, leukotoxin recombinant protein PL4 and hemolysin recombinant protein H2) and inactivated Fusobacterium necrophorum in preventing liver abscess. Four subcutaneous vaccines were formulated: vaccine 1 (43K OMP); vaccine 2 (PL4 and H2); vaccine 3 (43K OMP, PL4 and H2); and vaccine 4 (Inactivated F. necrophorum). 43K OMP, PL4 and H2 proteins were produced by using recombinant protein expression. To evaluate vaccine efficacy, we randomly allocated 50 BALB/c female mice to one of five different treatment groups: PBS control group, vaccine 1, vaccine 2, vaccine 3 and vaccine 4. Mice were vaccinated three times, with 14 days between each immunization. After immunization, the mice were challenged with F. necrophorum. The three key findings of this study are as follows: (1) Vaccine 3 has enabled mice to produce higher antibody titer following bacterial challenge, (2) in the liver pathology of mice, the vaccine 3 liver showed the least pathology, and (3) all four vaccines produced high levels of antibodies and cytokines in mice, but the level of vaccine 3 was the highest. Based on our results, it has been demonstrated that a mixture of F. necrophorum 43K OMP, PL4 and H2 proteins inoculated with mice can achieve protection against liver abscess in mice. Our research may therefore provide the basis for the development of a vaccine against F. necrophorum bovine infections.